Cytotoxic cardenolide and sterols from Calotropis gigantea - Jacinto, Sonia D. (Transactions of the National Academy of Science and Technology, 2011)
The dichloromethane extract from the leaves of Calotropis gigantea Linn. was strongly cytotoxic against non-small cell lung carcinoma (A549), colon carcinoma (HCT 116) and hepatocellular carcinoma (Hep G 2) and non toxic to non cancer Chinese hamster ovary cells (AA8). The extract afforded uscharin (1), 3,5,8-trihydroxy-24-methylcholest-6,22-diene (2), a mixture of (24R)-3-hydroxy-24-ethylcholest-5-en-7-one (3a) and (24S)-6-hydroxy-24-ethylcholest-4,22-dien-3-one (4a) and (24S)-24-ethylcholest-4,22-dien-3-one (4b). Compound 1 exhibited extreme cytotoxicity to A549, HCT 116 and Hep G 2 with IC50 of 0.003 μg/mL, 0.013 μg/mL, and 0.018 μg/mL, respectively, while sample 3 exhibited IC50 of 1.35 μg/mL, 4.46 μg/mL, and 3.83 μg/mL, respectively.